Síntese do complexo ferro (III) com ácido pirazina tetracarboxílico e aplicação como catalisador em reação fenton - Magalhães, Kassiana Teixeira (2016)
The amount of waste generated by industries has increased gradually in recent years. The proper disposal of residues has been an area of study of many researchers. Several organic compounds are considered potential contaminants of natural waters due to their high toxicity, difficult natural degradation and long persistence in the environment. Ways of recovery and reutilization as well as concepts that minimize the generation of wastes have been increasing widely. Organometallic compound of pyrazine carboxylic acid has proven to be of great interest in many areas. Herein, we studied the use of pyrazine tetracarboxylic acid ligand for complex formation with iron (Fe). The binder (C 8H4N2O8) was synthetized with the addition of Fe (complex) and tested as a catalyst in oxidation reactions of the organic model compound methylene blue (MB). Tetramethyl pyrazine was used in the synthesis, which was oxidized with potassium permanganate in order to form the ligand. The ligand (C 8H4N2O8) was then characterized to validate its formation. For the complex solution, it was used (C 8H4N2O8) and Fe (NO3)3.9H2O 0,01molL-1. After preliminary tests, it was found that the best ratio of Fe and the ligand was 2: 1. Through the oxidation tests, it could be seen that the complex has great potential for the degradation of different concentrations of MB. During only 20 minutes of reaction, approximately 60% of MB 500 mgL -1 was oxidized. The use of the complex was found to be an attractive alternative for oxidation of effluents with high organic compounds levels and contributes to the minimization of organic contaminants hazards in the environment.